5 The cardiac microrna miR-1 induces endothelial cell angiogenesis. (17th November 2015) - Kurusamy, S; Cadagan, D; Rowther, F; Wang, W; Redondo, JM; Cotton, JM; Armesilla, AL
Abstract : Ischaemic heart disease is the leading cause of morbidity and mortality in the Western world. Progression of the disease is associated with the growth and/or episodic rupture of atherosclerosis lesions leading to narrowing or occlusion of major coronary arteries. Arterial occlusion activates sprouting of pre-existing capillaries (angiogenesis) and the development of collateral arteries (arteriogenesis) to protect the myocardial tissue against the ischaemic condition. Unfortunately, the molecular mechanisms that control post-ischaemic neovascularization of the heart are large unknown. Emerging evidence indicates that acute ischaemia in patients with ST-segment-elevation myocardial infarction induces the release of microRNA miR-1 from injured cardiomyocytes. miRNA-1 promotes physiological angiogenesis during the embryogenesis of zebra fish but its role in post-natal angiogenesis in human endothelial cells has not been studied thus far. In this work, we show that adenoviral-mediated delivery of miR-1 into primary Human Umbilical Vein Endothelial Cells (HUVECs) resulted in an increase in proliferation, migration and the ability of the cells to form tubular-like structures in in vitro matrigel assays. These results suggest that cardiac microRNAs released by ischaemic cardiomyocytes might activate angiogenic events in neighbouring endothelial cells to promote the formation of new blood vessels. Thus, therapeutic interventions aimed to potentiate this process might have important clinical applications to facilitate fast perfusion of the infarcted heart. Acknowledgments This work was supported by RIHS, The Wolverhampton Coronary Aftercare Support Group (WCASG) Charity, and The Rotha Abraham Bequest Charity.